ISNI - International Standard Name Identifier - Ilie, Zanfir (Qualitative and Quantitative Methods in Libraries, 2019)
Choosing a single authorized form for a name to represent all the headings of a creator is a very difficult task for a librarian, if we take into account the fact that, throughout time, a creator could use several names, pseudonyms, literary pseudonyms, stage names, etc., in their various phases of the creation process, for the various fields in which they created or for the positions they held. Although the form variants point to the favoured one, researchers have come to the conclusion that another problem that hinders the identification of a creator is homonymy, which can cause confusion among users.